From Mushalla to Mosque: The Formation of South and Southeast Asian Muslim Communities in Japan - Amin, Ali (Al-Albab, 2019)
Since the 1980s, Japan has attracted Muslim immigrants, mainly from South and Southeast Asian countries. The emergence of these Islamic communities in Japan is reflected by the presence of around one hundred mosques and musallas (rooms or buildings for the performance of five daily prayers) on the Japanese archipelagos. This paper aims to discuss South and Southeast Asian Muslim communities in Japan, and the spaces used for their rituals and social activities as they have developed into full congregations able to support mosque construction and maintenance. I investigate how the transnational aspect of migration has shaped the architectural availability of places of prayer, and the development of the ummah (Muslim community). My data was collected from observation of Indonesian and Indian mosques in the greater Tokyo region between 2015 and 2017, and interviews with their congregations.